Electrical Properties of Two Types of Lithium-Based Glass Ceramics - Marko Jakovac; Mark Žic; Luka Pavić; Teodoro Klaser (University of Zagreb. School of Dental Medicine, 2022)
The dental ceramic materials are constantly being developed due to their continuous clinical application in the field of esthetic dentistry. Glass ceramics (GC) materials are also of special interest for dental application due to their specific properties; and thus, they can be applied as crowns, veneers and small bridges. Purpose: However, due to a variety of different GC materials, it is of keen interest to inspect their morphology and ion-diffusion, which also governs aging properties. Material and methods: In this study, two different GC materials were processed, i.e., lithium silicate (LS-10) and lithium disilicate (LS-20). The aforementioned properties can be inspected by using impedance spectroscopy (IS) and scanning electron microscopy (SEM). Results: SEM study suggested that LS-10 material is harder to mechanically process by computer-aided design/computer-aided manufacturing (CAD/CAM) technology. Furthermore, IS measurements showed that LS-20 (vs. LS-10) has more pronounced resistance properties. Conclusion: According to IS data, it was concluded that LS-20 (vs. LS-10) has more pronounced resistance properties that point out to hindered ion-diffusion and to better aging properties.